Apolipoprotein E Isoform-Dependent Effects on Human Amyloid Precursor Protein/Aβ-Induced Behavioral Alterations and Cognitive Impairments and Insoluble Cortical Aβ42 Levels - Holden, Sarah; Kundu, Payel; Torres, Eileen R. S.; Sudhakar, Reetesh; Krenik, Destine; Grygoryev, Dmytro; Turker, Mitchel S.; Raber, Jacob (Frontiers in Aging Neuroscience, 2022)
Mice expressing human Amyloid Precursor Protein (APP) containing the dominant Swedish and Iberian mutations (AppNL-F) or also Arctic mutation (AppNL-G-F) show neuropathology and hippocampus-dependent cognitive impairments pertinent to Alzheimer’s disease (AD) in mouse models at 18 and 6 months of age, respectively. Apolipoprotein E, involved in cholesterol metabolism, plays an important role in maintaining the brain. There are three human apolipoprotein E isoforms: E2, E3, and E4. Compared to E3, E4 increases while E2 protects against AD risk. At 6 months of age, prior to the onset of plaque pathology, E3, but not E4, protected against hAPP/A-induced impairments in spatial memory retention in the Morris water maze. However, these earlier studies were limited as hapoE was not expressed outside the brain and E3 or E4 was not expressed under control of an apoE promotor, E2 was often not included, hAPP was transgenically overexpressed and both mouse and hAPP were present. Therefore, to determine whether apoE has isoform-dependent effects on hAPP/A-induced behavioral alterations and cognitive impairments in adult female and male mice at 6 and 18 months of age, we crossed AppNL-G-F and AppNL-F mice with E2, E3, and E4 mice. To distinguish whether genotype differences seen at either time point were due to main effects of hAPP, hapoE, or hAPP x hapoE genetic interactions, we also behavioral and cognitively tested E2, E3, and E4 female and male mice at 6 and 18 months of age. We also compared behavioral and cognitive performance of 18-month-old AppNL-G-F and AppNL-F female and male mice on a murine apoE background along with that of age—and sex-matched C57BL/6J wild-type mice. For many behavioral measures at both time points there were APP x APOE interactions, supporting that apoE has isoform-dependent effects on hAPP/A-induced behavioral and cognitive performance. NL-G-F/E3, but not NL-G-F/E2, mice had lower cortical insoluble A42 levels than NL-G-F/E4 mice. NL-F/E3 and NL-F/E2 mice had lower cortical insoluble A42 levels than NL-F/E4 mice. These results demonstrate that there are apoE isoform-dependent effects on hAPP/A-induced behavioral alterations and cognitive impairments and cortical insoluble A42 levels in mouse models containing only human APP and apoE.